1992
DOI: 10.1111/j.1365-2362.1992.tb01446.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intravenous polyunsaturated phosphatidylcholine infusion on insulin receptor processing and lipid composition of erythrocytes in patients with liver cirrhosis

Abstract: The aim of this study was to determine whether insulin receptor processing capabilities of human erythrocytes could be improved by changing the cell membrane lipid composition using an intravenous infusion of polyunsaturated phosphatidylcholine. Thirteen cirrhotics were submitted to the i.v. infusion of phosphatidylcholine (2 g day-1 for 3 days). Both erythrocyte lipid composition and insulin receptor processing ability were examined at the beginning of the study and at 0, 3 and 11 days after the end of the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…However, it is still not clear which component in the soybean is involved in cytoprotection. It should be underlined that phosphatidylcholine (PPC), a major component of the phospholipid fractions of the islet cells (Diaz et al 1988), exerts diverse biological actions including receptor processing for insulin responsiveness (Clore et al 1998(Clore et al ,2000, cell growth, and transformation (Turk et al 1986;Larrodera et al 1990;Cantafora et al 1992). PPC extracted from soybean is mainly composed of phosphatidylcholine containing two molecules of linoleic acid.…”
mentioning
confidence: 99%
“…However, it is still not clear which component in the soybean is involved in cytoprotection. It should be underlined that phosphatidylcholine (PPC), a major component of the phospholipid fractions of the islet cells (Diaz et al 1988), exerts diverse biological actions including receptor processing for insulin responsiveness (Clore et al 1998(Clore et al ,2000, cell growth, and transformation (Turk et al 1986;Larrodera et al 1990;Cantafora et al 1992). PPC extracted from soybean is mainly composed of phosphatidylcholine containing two molecules of linoleic acid.…”
mentioning
confidence: 99%
“…This was also observed in the case of hyperlipidemias where the value of the correlation was affected by the cho lesterol content in the membrane phospholipids (see the R values in table 4). Again, as in the case of liver cirrhosis [6] we observed in this study that other lipid composition parameters appear to play a role. The difference in insulin receptor regulation between type lib and Ha hyperlipid émies did not seem to be determined by a difference in the CH/PL ratios, but rather by the phospholipid class com position.…”
Section: Discussionmentioning
confidence: 47%
“…In previous papers we have reported that lipid membrane alterations caused by severe liver pathologies strongly affect insulin-receptor process ing capabilities [22,26], Furthermore, we demonstrated that the lipid parameters mentioned above could be ma nipulated, both in vivo and in vitro, by lipid exchanges with liposomes containing polyunsaturated molecular species of PC. This has intriguing ramifications with the diet-related alterations in glucose tolerance and the devel opment of noninsulin-dependent diabetes mellitus [6]. The present study started with the assessment in dys lipidémie patients of those membrane lipid parameters that our previous studies with red blood cells of cirrhotic patients suggested to be involved in the insulin receptor processing, i.e., the molar ratio of CH/PL, the distribution of the major lipid classes and the degree of saturation of their fatty acids.…”
Section: Lipid Analysesmentioning
confidence: 99%